Development of reverse transcription loop-mediated isothermal amplification for detection of Rhinovirus C - Wong, Yien Ping (2019)
During worldwide surveillance for emerging respiratory viruses in the late 2000s, Rhinovirus C (RV-C) was identified from previously unseen to clinical detection using molecular detection. RV-C is closely associated with severe hospitalized infections and exacerbation of chronic pulmonary diseases (COPDs). However, unlike RV-A and –B, RV-C is unculturable in standard tissue culture. Therefore, molecular detection became important for the diagnosis of RV-C. Several molecular diagnostics assays such as reverse transcription polymerase chain reaction (RT-PCR) either single or multiplex and probe-based real-time PCRs are made available. However, only several laboratories have access to these diagnostic assays due to their costs and time-consuming process, therefore unavailable and unaffordable, for accurate and rapid virological confirmation. This study used a new molecular approach, known as loop-mediated isothermal amplification (LAMP) for rapid detection and differentiation of RVC from -A and -B. LAMP is known for its rapid amplification of target template under isothermal conditions, visible naked eyes observation for positive results, much simpler, low cost, and rapid in the disease diagnosis. In this study, new oligonucleotides targeting 5’UTR were designed based on 20 RVC sequences, comprising available Malaysia sequences and neighboring countries such as Hong Kong, China and Thailand. Four sets of primers (Set 1-4) were specially designed for amplification using free online software and all sets of primer were tested. Selected primers were tested with temperatures ranging from 60-65˚C, varying concentrations of MgSO4 (2-12 mM) and betaine (0-1.2 M), primer concentration ratios between outer primer to inner (1:1-1:12) and reaction time for optimal LAMP reaction. Of four set of primers tested, only Set 1 primer showed positive amplification whereas Set 2-4 showed negative amplification. Hence, Set 1 primer was used for further optimization. LAMP with Set 1 primer detected RV-C at 61˚C for 40 minutes of incubation, of approximately three times faster than PCR. The final LAMP assay comprised 5 pmol each of outer primer F3 and B3, 40 pmol each of inner primer FIP and BIP (primer ratio of 1:8), 8 mM of magnesium ion (Mg2+) and 0.8 M betaine. Set 1 primer showed high LAMP efficiency and sensitivity, with a quantifiable viral load as low as 104 copies of RNA within 40 minutes. This RT-LAMP assay was evaluated with known RV-As, -Bs, -Cs and other respiratory virus infected clinical samples. The RT-LAMP was able to detect all RV-C isolates. RT-PCR was carried out in parallel with LAMP outer primers (F3 and B3) and amplicons were purified and sequenced. Sequences analysis indicated RV-Cs, thus further verifying the specificity of the developed RT-LAMP. The present study offered better detection of RVCs as compared to existing methods. However, improvements such as primer design and inclusion of more samples are required for differentiation of RV-C from RV-A and RV-B.